A chelated iron desulfurizer

By using chelated iron desulfurizer combined with polyetheramine tetraacetate and other chelating agents, the problems of environmental pollution and health risks of chelating agents in the prior art are solved, and efficient gas desulfurization effect and good biodegradation performance are achieved.

CN116218575BActive Publication Date: 2025-04-22SHENZHEN BRANCH CHINA NAT OFFSHORE OIL CORP +1

Patent Information

Application Number
CN202310135743.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-04-22
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

Chelating agents such as EDTA, NTA and DTPA used in existing gas desulfurizers have environmental pollution and health risks, and their biodegradability is poor, making it difficult to meet the development requirements of environmental protection technology.

Method used

A chelated iron desulfurizer is used to combine polyetheramine tetraacetate with N,N-diacetylcarboxylic acid ethylenediamino-3-hydroxysuccinic acid, polycarboxylic acid chelating agent or amino acid-derived chelating agent to form a stable chelating iron solution through a system composed of high-valent soluble iron salt and pH buffering agent.

Benefits of technology

The desulfurization efficiency comparable to EDTA and NTA is achieved, the calcium and iron chelation rates are improved, the total iron loss rate and chelating agent loss are reduced, the iron ion regeneration capacity is significantly improved, and the chelating agent has good biodegradability and environmental protection properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a chelated iron desulfurizer, which is composed of a high-price soluble iron salt, a chelating agent, a pH buffer and water, wherein the chelating agent is a compound of sodium polyetheramine tetraacetate and at least one of N,N-diethylcarboxylic acid-based ethylenediamino-3-hydroxysuccinic acid, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent; or the chelating agent is a compound of tetrasodium N,N-diethylcarboxylic acid-based ethylenediamino-3-hydroxysuccinic acid and at least one of sodium polyetheramine tetraacetate, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent. Compared with the existing commonly used desulfurizers EDTA or NTA, the chelating ability of the present application's chelated iron desulfurizer is significantly improved, the iron ion regeneration ability is significantly enhanced, and the desulfurization effect is comparable to EDTA or NTA.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a gas desulfurization agent, specifically to a gas desulfurization agent to which a new green biodegradable chelating agent is added, which can complex trivalent iron ions to form a stable chelated iron solution and can be widely used in gas desulfurization fields such as natural gas desulfurization. Background Art

[0002] Most of the energy used by humans today is non-renewable coal, oil and natural gas. At present, the domestic sulfur-containing gas field (sulfur mass fraction is 2% to 4%) accounts for about 60% of the national gas production, and most sulfides are harmful impurities to natural gas, especially hydrogen sulfide, which not only causes serious corrosion to important equipment such as storage tanks and pipelines, but also seriously endangers nature and human health. To fundamentally solve these problems, it is necessary to consider removing hydrogen sulfide from natural gas.

[0003] At present, there are two main methods for removing gas-phase hydrogen sulfide: dry method and wet method. Among them, the dry method uses the reducibility and flammability of hydrogen sulfide to desulfurize or directly burn it with solid oxidants or adsorbents, including the Claus process, iron oxide method, activated carbon method, etc. The Claus process is the most widely used dry process. The most widely used wet process is the traditional complex iron desulfurization process. This process uses trivalent complex iron ions as catalysts to convert H2S dissolved in the desulfurization liquid into elemental sulfur. At the same time, the catalyst is reduced to divalent complex iron ions, and then the divalent complex iron ions are re-oxidized to trivalent complex iron ions using air as an oxidant for recycling.

[0004] The chelating agents used to complex iron ions have gone through more than half a century of development, from the initial EDTA chelating agents to the later organophosphine chelating agents, and then to the recent new amino acid chelating agents.

[0005] Ethylenediaminetetraacetic acid (EDTA), the original chelating agent in the complex iron desulfurization process, is generally considered non-toxic to mammals and aquatic organisms, but the environmental impact of EDTA has caused concern in part due to its overuse and its increased concentration in various water sources (e.g., streams, oceans, aquifers, etc.). For example, high concentrations of EDTA in water sources can dissolve heavy metals from sediments and soils, thereby increasing the mobility of heavy metals and disrupting the natural metal distribution in the environment. The increased mobility of heavy metals in water sources can also increase health risks (such as toxicity) to humans, plants, animals and other organisms. In addition, EDTA degrades relatively slowly and is therefore generally not considered a readily biodegradable chelating agent. It is not easily biodegradable, EDTA can be toxic to plants and microorganisms, affecting their survival, and can cause secondary pollution. It has a high potential environmental risk and is not suitable for most green labels. Some EU countries prohibit or restrict the use of EDTA. There is no EDTA in British household detergents. Germany has significantly reduced the content of EDTA in the ecological environment since 1991. Wastewater laws in Germany and Austria prohibit the use of EDTA in most industrial wastewaters. Switzerland sets maximum concentrations for EDTA in relevant applications and prohibits its use in cleaning agents for government and public buildings.

[0006] Nitrilotriacetic acid (NTA), a chelating agent commonly used in the complex iron desulfurization process, has a price advantage and is a suspected carcinogen. Its use is restricted by regulations. In the global harmonized classification and labeling system for hazardous chemicals, NTA is listed as a suspected carcinogen and is accompanied by a hazardous chemical label similar to a chest explosion. In the United States, NTA content must be labeled as a suspected carcinogen when it exceeds 0.1%. In the European Union, NTA is included in the European Commission's 31st ATP (Adaptive Technological Advances) classification catalog of hazardous compounds. Products with NTA content exceeding 5% are immediately and automatically classified as R40 hazardous goods and affixed with temporary labels to remind consumers that "limited evidence shows carcinogenicity." Products containing NTA are also not suitable for affixing various popular green labels.

[0007] The chelating agent diethylenetriaminepentaacetic acid (DTPA) used in the complex iron desulfurization process may be harmful to the human body and fetus, which greatly limits its scope of application.

[0008] The phosphate used in the complex iron desulfurization process is mainly sodium tripolyphosphate (STPP), but because the discharge of phosphorus causes eutrophication of lakes and rivers and other environments, countries have also issued relevant regulations to restrict the use of phosphorus-containing chemicals, so phosphate chelating agents are gradually fading out of the market. Washington State in the United States banned phosphates in all detergents from the first quarter of 2008. Canada is considering reducing the content of phosphoric acid in household and industrial products to below 0.5% from 2010. France has levied a tax on the use of STPP.

[0009] Therefore, the above chelating agents can no longer meet the development requirements of social science and technology and environmental protection technology. The function of chelating agents for complexing iron ions is no longer limited to chelating effect, but develops towards diversity while exerting the performance of chelating agents. The so-called diversity means that while complexing iron ions, it is environmentally friendly, biodegradable, and can increase the scale inhibition rate of calcium carbonate. Summary of the invention

[0010] Based on the above technical problems, the present application provides a chelated iron desulfurizer, which is composed of a high-valent soluble iron salt, a chelating agent, a pH buffer and water, wherein the molar ratio of the chelating agent to the iron salt is 1.0:1-5:1; the pH value of the chelated iron is 8.0-13.5; the chelating agent is a compound of sodium polyetheramine tetraacetate and at least one of N,N-diacetic acid-based ethylenediamino-3-hydroxysuccinic acid, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent; or the chelating agent is a compound of tetrasodium N,N-diacetic acid-based ethylenediamino-3-hydroxysuccinic acid and at least one of sodium polyetheramine tetraacetate, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent.

[0011] Preferably, sodium polyetheramine tetraacetate and tetrasodium N,N-diacetylethylenediamino-3-hydroxysuccinate are compounded in any ratio.

[0012] The preferred compounding ratio of polyetheramine tetraacetate sodium or N,N-diacetylethylenediamino-3-hydroxysuccinate tetrasodium to the polycarboxylic acid chelating agent is 1:0.05 to 1:0.5.

[0013] The preferred compounding ratio of polyetheramine tetraacetic acid sodium or N,N-diethylcarboxylic acid ethylenediamino-3-hydroxysuccinic acid tetrasodium and amino acid derivative chelating agent is (1-5): (1-3).

[0014] The polycarboxylic acid chelating agent is selected from polyacrylic acid or its salt, polymethacrylic acid or its salt, water-soluble polymaleic anhydride or fumaric acid-propylene sulfonic acid binary copolymer; wherein the average molecular weight of polyacrylic acid or its salt or polymethacrylic acid or its salt is 4000-5000; the molecular weight of water-soluble polymaleic anhydride is 400-800. Since there are a large number of carboxylic acids in the polycarboxylic acid chelating agent molecules, the carboxyl oxygen atom has the ability to form a coordination bond, and the adjacent carboxyl groups can form a chelate ring with metal ions and stably exist in water. The polycarboxylic acid chelating agent can be used in combination with other chelating agents to achieve a synergistic effect.

[0015] The amino acid derived chelating agent is obtained by chemical synthesis, and the amino acid in the amino acid salt is selected from glutamic acid, alanine, glycine, leucine, and aspartic acid. More specifically, the amino acid derived chelating agent is selected from one or more of epoxysuccinic acid-2-(hydroxyimino)malonate sodium copolymer (average molecular weight 180-400), tetrasodium iminodisuccinate, sodium aspartic acid diacetate, tetrasodium glutamic acid diacetate (GLDA), trisodium methylglycine diacetate (MGDA), dihydroxyethylglycine, and ethylenediamine disuccinic acid (EDDS). The amino acid derived chelating agent contains multiple functional groups such as amine and carboxyl, has good chelating properties, can better combine with metal ions, and has high chemical stability; it also has good water solubility and good biodegradability; it has a certain corrosion inhibition effect on carbon steel and can be used as a substitute for the chelating agent EDTA.

[0016] The high-valent soluble iron salt is FeCl3, Fe(CH3COO)3, Fe(NO3)3, ammonium ferric sulfate or Fe2(SO4) 3、 At least one of ferric citrate and ammonium ferric citrate.

[0017] The pH buffer is one or more of NaOH, Na2CO3, NaHCO3, KOH, K2CO3, KHCO3, ammonia water or an organic base.

[0018] By adopting the above technical solutions, the desulfurization efficiency can be comparable to that of EDTA and NTA; the calcium and iron chelation rates are greater than those of EDTA or NTA; the total iron loss rate and chelating agent loss are lower than those of EDTA or NTA; and the iron ion regeneration capacity is significantly improved.

[0019] The present application also provides a preparation method of a chelated iron desulfurizer, which is carried out according to the following steps: at 25-30°C, first add a high-valent iron salt and deionized water into a reactor with a heating and stirring function, then add a quantitative chelating agent, control the temperature, and add a pH buffer while stirring until all the mixture is dissolved. The pH value of the chelated iron desulfurizer is adjusted to between 9.0 and 13.5 with the pH buffer, and the temperature is raised to 50-100°C. The reaction is continued with stirring for 4-8 hours to obtain the chelated iron desulfurizer.

[0020] The advantages of the present invention are:

[0021] (1) The chelating agent used in the chelated iron desulfurizer of the present application not only has a strong chelating ability, but also has a corrosion inhibition effect and a bactericidal function, which can reduce the amount of corrosion inhibitors and bactericides to a certain extent, such as tetrasodium 3-hydroxy-2,2′-iminodisuccinate (HIDS) or glutamic acid oxalic acid (GLDA).

[0022] (2) The chelating agent used in the chelated iron desulfurizer of the present application is green and environmentally friendly, and its raw materials are characterized by high efficiency, safety and sustainability. The safety here means that toxicological studies have shown that the toxicity is safer than that of EDTA or NTA, and it has high biodegradability.

[0023] (3) The chelated iron desulfurizer of the present application has good regeneration performance and high desulfurization efficiency.

[0024] (4) The chelated iron desulfurizer of the present application not only has a good desulfurization effect, but also reduces the loss of the chelating agent, thereby reducing the salt content of the desulfurization liquid. It is of great significance in improving the quality of the final sulfur, increasing the added value of by-products, and reducing production costs. DETAILED DESCRIPTION

[0025] Source of raw materials

[0026] The polycarboxylic acid chelating agent mentioned in the present application is selected from polyacrylic acid, sodium polyacrylate, polymethacrylic acid, water-soluble polymaleic anhydride or fumaric acid-propylene sulfonic acid binary copolymer; wherein the average molecular weight of polyacrylic acid, sodium polyacrylate or polymethacrylic acid is 4000-5000; the molecular weight of water-soluble sodium polymaleate is 400-800.

[0027] The materials used in the embodiments of the present application are all conventional commercially available reagents: the chelating agent is a conventional aqueous solution with a mass percentage of about 40%, for example, sodium polyacrylate is a 40% aqueous solution with a molecular weight distribution range of 4000-5000; the amino acid chelating agent GLDA is a 38% aqueous solution.

[0028] The molecular weight of the polyetheramine tetraacetate used in the present application is 500-800.

[0029] The chelating agent mentioned in the quantitative chelating agent or the molar ratio of the chelating agent to the iron ion mentioned in the present application refers to the total amount of the chelating agent after compounding one or more chelating agents.

[0030] The chelating agent loss mentioned in the present application refers to the difference between the weight of the chelating agent in the desulfurization agent solution before desulfurization and the weight of the chelating agent in the desulfurization agent solution after desulfurization.

[0031] The average molecular weight of the sodium epoxysuccinate-2-(hydroxyimino)malonate copolymer used in the present application is 180-400.

[0032] The HAB mentioned in the present application refers to tetrasodium N,N-diethylcarboxylate ethylenediamino-3-hydroxysuccinate.

[0033] Experimental methods:

[0034] 1. The preparation method of the chelated iron desulfurizer of the present application is carried out according to the following steps: at 25-30°C, first add a high-valent iron salt and deionized water to a reactor with a heating and stirring function, then add a quantitative chelating agent, control the temperature, add a pH buffer while stirring until it is completely dissolved, adjust the pH value of the chelated iron desulfurizer to between 9.0 and 13.5 with a pH buffer, raise the temperature to 50-100°C, continue stirring the reaction for 4-8 hours, and obtain the chelated iron desulfurizer.

[0035] 2. Determination of calcium ion chelation value

[0036] Weigh 2g of the sample to be tested into a 250mL wide-mouth conical flask, add about 100mL of deionized water, then add 10mL of 20g / LNa2CO3 solution, and add water to the 150mL mark. Adjust the pH to 11, and titrate with 10mg / mLCaCl2 standard solution under magnetic stirring until a slightly turbid permanent precipitate is produced. Keep the pH at around 11 during the titration process. The volume of calcium chloride solution consumed is V, and the calcium chelation value is expressed in mg / g of calcium carbonate.

[0037] X=V*2.5*C / m;

[0038] V: volume of calcium chloride standard solution consumed by the sample, in mL;

[0039] C: concentration of calcium chloride standard solution, unit: mg / mL;

[0040] m: sample mass, unit: g.

[0041] 3. Iron ion chelation value determination method: sulfosalicylic acid colorimetric determination

[0042] Accurately weigh 1.0g of the sample to be tested, dissolve it in deionized water, transfer it to a 100mL volumetric flask and dilute to the mark, shake it well and set aside for testing. Transfer 2mL of the prepared sample solution to a 50mL conical flask, add 30mL of water and 5 drops of 2% sulfosalicylic acid, and titrate with 0.01mol / L ammonium ferric sulfate standard solution until the solution changes from colorless to slightly reddish as the end point. The calculation formula is as follows:

[0043] X=V*C*159.6*50 / m

[0044] V: volume of ammonium ferric sulfate solution consumed by the sample, unit: mL;

[0045] C: concentration of ammonium ferric sulfate standard solution, unit: mol / L;

[0046] m: sample mass, unit: g.

[0047] 4. Chelated iron desulfurizer performance test

[0048] H2S removal evaluation device: The desulfurizer prepared above is configured into a 350-500ppm desulfurization liquid for desulfurization performance test. In the preparation of the desulfurization liquid, a certain amount of chelating agent needs to be added. The compounding ratio of the compound chelating agent and the ratio of chelating agent / Fe are added according to the proportions of each test example or embodiment. In the H2S removal evaluation device, a glass tube with a diameter of 8cm and a height of 40cm is used to evaluate the desulfurizer of each test example and embodiment. A gas distributor is set at the bottom of the glass tube, and a hydrogen sulfide tail gas detection device is connected behind the absorption tube.

[0049] Experimental conditions:

[0050] Raw gas composition: 20% (volume fraction) H2S, N2 as balance gas;

[0051] Acid gas flow rate: 0.4L / min;

[0052] Air flow: 10L / min;

[0053] Pressure: normal pressure;

[0054] Temperature: room temperature;

[0055] Absorption and regeneration temperature: 40-50°C;

[0056] Solution pH: 8.5;

[0057] A hydrogen sulfide detector was used to detect the hydrogen sulfide concentration at the outlet in real time. Under the above experimental conditions, the reaction lasted for 100 hours, and the desulfurization solution was sampled and analyzed.

[0058] 5. Desulfurizer regeneration performance test, reaction conditions: total iron content is 500ppm, the compounding ratio of the compound chelating agent and the ratio of chelating agent / Fe are added according to the ratio of each test example or embodiment, pH=9.50, desulfurization catalyst solution 1.5L, acid gas conditions: 20%H2S 50mL / min, air conditions: 1.2L / min, first absorb the acid gas reaction, and then introduce air for regeneration reaction. A hydrogen sulfide detector is used to detect the hydrogen sulfide concentration at the outlet in real time. During the regeneration reaction, the regeneration process is terminated by detecting that the ORP value returns to the initial value or does not change, and the time required for the regeneration reaction is recorded.

[0059] 6. The ORP value in this application is tested by ORP detector, and it is the ORP value after the absorption reaction for 30 minutes, in mV, with an error range of ±1.5mV.

[0060] Test Example 1: Compounding of polyetheramine tetraacetate sodium and polycarboxylic acid

[0061] Test Example 1.1 Sodium polyetheramine tetraacetate and sodium polyacrylate

[0062] Sodium polyetheramine tetraacetate, sodium polyacrylate, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ion was 4.5wt%, the molar ratio of the two chelating agents was compounded and added according to Table 1.1, the molar ratio of chelating agent / Fe was 1.5, the pH value was adjusted to 9.5 with NaOH, and the mixture was mixed and reacted for 4h according to the preparation method. The molar ratio of the two chelating agents was as shown in Table 1.1:

[0063] Table 1.1: Test Example 1.1 Chelating agent ratio

[0064]

[0065] The chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time (min) when H2S tail gas is greater than 250ppm, ORP value (mV) and regeneration of iron ions (time / min) of Test Example 1.1 were tested and the results are shown in Table 1.2.

[0066] Table 1.2 Test Example 1.11 Test Example 1.12 Test Example 1.13 Test Example 1.14 Test Example 1.15 Test Example 1.16 Chelating power (calculated as Ca, mg / g) 89.9 121.9 135.6 134.7 138.1 136.4 Chelating power (in terms of Fe, mg / g) 92.9 133 140.5 139.4 141.1 138.7 Desulfurization effect / % 99. 37 99.89 99.92 99.95 99.98 99.96 Total iron loss rate / % 8.9 6.4 5.3 6.5 5.5 5.7 Chelating agent loss / g / L 2.6 0.83 0.79 0.51 0.65 0.77 <![CDATA[H2S tail gas greater than 250 ppm / min]]> 31 25 27 26 26 30 ORP value / mV 426.6 -444.8 -444.2 447.2 445.1 478.4 Regeneration time / min 102 80 77 76 78 72

[0067] By analyzing the results in Table 1.2, it can be seen that after sodium polyetheramine tetraacetate and polyacrylic acid (sodium), if the content of sodium polyacrylate is too low, the compounding effect cannot be achieved, which is mainly reflected in the low chelating force (chelating force of calcium ions and iron ions), and the loss of chelating agent (total iron loss rate and chelating agent loss) increases significantly, which may be because the chelating ability of carboxyl is greater than that of hydroxyl and amine groups. However, when sodium polyacrylate reaches a certain amount, its chelating value and the loss of chelating agent tend to be stable and no longer increase significantly, and the biodegradability of sodium polyacrylate is weaker than that of sodium polyetheramine tetraacetate. Therefore, from the perspective of environmental protection, the addition amount of sodium polyacrylate is no longer increased.

[0068] Test Example 1.2 Sodium polyetheramine tetraacetate and sodium polymethacrylate

[0069] The difference in Test Example 1.1 is that sodium polymethacrylate is used instead of sodium polyacrylate. The chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time (min) when H2S tail gas is greater than 250ppm, ORP value (mV) and regeneration of iron ions (time / min) of Test Example 1.2 were tested. The results showed that after sodium polyetheramine tetraacetate and sodium polymethacrylate were compounded, they showed similar results and rules as sodium polyacrylate within the above ratio range, and there was no significant difference, which will not be repeated here.

[0070] Test Example 1.3 Compounding of polyetheramine tetraacetic acid sodium and water-soluble polymaleic anhydride

[0071] The difference of Test Example 1.1 is that water-soluble polymaleic anhydride is used to replace sodium polyacrylate. The chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S tail gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) of Test Example 1.3 were tested, and the results are shown in Table 1.3.

[0072] Table 1.3 Test Example 1.31 Test Example 1.32 Test Example 1.33 Test Example 1.34 Test Example 1.35 Test Example 1.36 Chelating power (calculated as Ca, mg / g) 101.3 128.2 138.6 144.5 148.1 146.4 Chelating power (in terms of Fe, mg / g) 105.4 134.2 146.1 149.1 150.0 148.8 Desulfurization effect / % 99.84 99.89 99.94 99.97 99.98 99.96 Total iron loss rate / % 8.7 6.5 6.2 5.9 6.4 5.8 Chelating agent loss / g / L 2.1 0.77 0.69 0.57 0.55 0.61 <![CDATA[H2S tail gas greater than 250 ppm / min]]> 31 25 27 26 26 30 ORP value / mV -483.1 -474.9 -484.5 -487.2 -485.1 -488.4 Regeneration time / min 104 69 71 66 68 65

[0073] By analyzing the results in Table 1.3, it can be seen that after the compounding of sodium polyetheramine tetraacetate and water-soluble polymaleic anhydride, when the ratio of sodium polyetheramine tetraacetate to water-soluble polymaleic anhydride is 1:0.03, compared with Test Example 1.1 (comparing water-soluble polymaleic anhydride with polyacrylic acid), the chelating force (chelating force of calcium ions and iron ions) is improved, and the loss of chelating agent (total iron loss rate and chelating agent loss) is further reduced. This may be because the chelating performance of water-soluble polymaleic anhydride is slightly higher than that of sodium polyacrylate. However, compared with sodium polyacrylate, the performance patterns of water-soluble polymaleic anhydride after compounding with sodium polyetheramine tetraacetate are similar, which mainly affects the chelating force and the loss of chelating agent.

[0074] Test Example 1.4 Compounding of sodium polyetheramine tetraacetate and fumaric acid-propylene sulfonic acid copolymer

[0075] The difference in Test Example 1.1 is that fumaric acid-propylene sulfonic acid dipolymer is used to replace sodium polyacrylate. The chelating power (calculated as Ca, mg / g), chelating power (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S tail gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) of Test Example 1.4 were tested, and the results are shown in Table 1.4.

[0076] Table 1.4 Test Example 1.41 Test Example 1.42 Test Example 1.43 Test Example 1.44 Test Example 1.45 Test Example 1.46 Chelating power (calculated as Ca, mg / g) 103.3 130.3 139.1 143.9 149.1 147.6 Chelating power (in terms of Fe, mg / g) 109.4 136.2 150.4 149.9 149.1 151.2 Desulfurization effect / % 99. 79 99.93 99.99 99.95 99.97 99.96 Total iron loss rate / % 8.3 5.7 6.0 5.1 4.6 4.8 Chelating agent loss / g / L 1.8 0.57 0.63 0.52 0.55 0.56 <![CDATA[H2S tail gas is greater than 250 ppm / min]]> 28 25 27 26 26 30 ORP value / mV -473.9 -484.1 -475.7 -492.7 -488.8 -478.3 Regeneration time / min 100 70 70 60 65 75

[0077] Comparison of Table 1.3 and Table 1.4 shows that compared with water-soluble polymaleic anhydride and fumaric acid-propylene sulfonic acid binary copolymer, after compounding with polyetheramine tetraacetic acid, the effects are comparable in chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S exhaust gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min).

[0078] Test Example 2 Compounding of Polyetheramine Tetraacetic Acid Sodium and HAB

[0079] Mix sodium polyetheramine tetraacetate, tetrasodium N,N-diacetylated ethylenediamino-3-hydroxysuccinate (HAB), NaOH, Fe(NO3)3·9H2O and water. The weight percentage of iron ions is 4.5wt%. The molar ratio of the two chelating agents is compounded and added according to Table 2.1. The molar ratio of chelating agent / Fe is 1.5. The pH value is adjusted to 9.5 with NaOH. Mix and react for 4 hours according to the preparation method to obtain a chelated iron desulfurizer.

[0080] The chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time (min) when H2S tail gas is greater than 250ppm, ORP value (mV) and regeneration of iron ions (time / min) of Test Example 2 were tested and the results are shown in Table 2.1.

[0081]

[0082] By analyzing the results in Table 2.1, it can be seen that there is no significant difference in the parameters of polyetheramine tetraacetate sodium and N,N-diacetylated ethylenediamino-3-hydroxysuccinate tetrasodium (HAB) within the above proportion range, so the two can be compounded in any ratio.

[0083] Sodium polyetheramine tetraacetate and tetrasodium N,N-diacetylated ethylenediamino-3-hydroxysuccinate (HAB) were used as chelating agents respectively, and their chelating power (calculated as Ca, mg / g), chelating power (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S exhaust gas was greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) were tested. The obtained values ​​are shown in Table 2.2.

[0084] Table 2.2 Polyetheramine tetraacetate sodium HAB Chelating power (calculated as Ca, mg / g) 80 83.3 Chelating power (in terms of Fe, mg / g) 88.2 87.1 Desulfurization effect / % 99.89 99.91 Total iron loss rate / % 10.2 9.8 Chelating agent loss / g / L 0.95 0.91 <![CDATA[H2S tail gas greater than 250 ppm / min]]> 20 21 ORP value / mV -425.4 -432.8 Regeneration time / min 90 90

[0085] By comparing Table 2.1 and Table 2.2, it can be seen that the chelating force of sodium polyetheramine tetraacetate is significantly improved after compounding with tetrasodium N,N-diacetylated ethylenediamino-3-hydroxysuccinate (HAB). In addition, the desulfurization effect of sodium polyetheramine tetraacetate is also significantly improved.

[0086] Test Example 3 Compounding of polyetheramine tetraacetate sodium and amino acid derivatives

[0087] The difference from Experimental Example 1 is that the polycarboxylic acid chelating agent in Example 1 is replaced by an amino acid derivative chelating agent, and the ratio of polyetheramine tetraacetic acid sodium to the amino acid derivative is set to 6:1, 5:1, 3:1, 1:1, 1:3 and 1:5. The amino acid derivative chelating agent used in this experimental example specifically includes the following compounds: epoxysuccinic acid-2-(hydroxyimino)malonate sodium copolymer (average molecular weight 180-400), tetrasodium iminodisuccinate, sodium aspartic acid diacetate, tetrasodium glutamic acid diacetate (GLDA), trisodium methylglycine diacetate (MGDA), dihydroxyethylglycine, ethylenediamine disuccinic acid (EDDS).

[0088] The compounding of sodium polyetheramine tetraacetate and amino acid derivatives takes the compounding result of sodium polyetheramine tetraacetate and EDDS as an example, and the results of the tests on chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S tail gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) are shown in Table 3.

[0089]

[0090] Analyzing the data in Table 3, when the ratio of polyetheramine tetraacetic acid sodium to N,N-diacetylethylenediamino-3-hydroxysuccinate tetrasodium (HAB) is too large (6:1), the viscosity of the desulfurizer increases, which reduces the reaction rate and significantly prolongs the time when the H2S tail gas is greater than 250ppm / min. When the ratio is too small, the iron ions will precipitate and the desulfurization effect will be reduced, and the total iron loss rate and chelating agent loss will increase.

[0091] Test Example 4 Compounding of HAB with polycarboxylic acids and amino acid derivatives

[0092] Based on the experimental results of Test Examples 1-3 and the test results of chelating power (calculated as Ca, mg / g), chelating power (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time (min) when H2S tail gas is greater than 250ppm, ORP value (mV) and regeneration of iron ions (time / min) of polyetheraminetetraacetic acid and HAB, we infer that polyetheraminetetraacetic acid and HAB can be compounded arbitrarily, and their properties are relatively similar. Therefore, it is possible that the compounding of HAB with polycarboxylic acid chelating agents and amino acid derivatives will be similar to the results of polyetheraminetetraacetic acid sodium. Therefore, Test Examples 1-3 were repeated using HAB instead of polyetheraminetetraacetic acid, and the results were consistent with the inference, so they are omitted here.

[0093] Test Example 5: Chelating agent / Fe molar ratio verification

[0094] The chelating agent compositions of Test Examples 1.13, 1.33, 2.3 and 3.13 are used as chelating agents, and the molar ratios of chelating agent / Fe are set at 1:1, 2:1, 3:1, 4:1 and 5:1. When the chelating agent is too little, complete complexation cannot be achieved. When the chelating agent is too much, the viscosity of the desulfurizer increases, which is not conducive to the reaction, which is specifically reflected in the extension of the desulfurization time.

[0095] Test Example 6 pH Investigation of Chelated Iron Desulfurizer

[0096] In the pH investigation experiment, the pH values ​​were set at 8.0, 9.0, 10, 11, 12 and 13.5 respectively, and no abnormal situation similar to the usual chelated iron desulfurizer occurred, which was in line with the pH application range of the conventional chelated iron desulfurizer. When the pH value was too low, below 8.0, alkali was needed to adjust the pH value, because the chelating ability was significantly reduced when the pH value was too low, mainly because the chelating agent had low solubility under acidic conditions. When the pH increased by 11, its solvent type basically tended to be stable; if the pH was too high, above 12, the chelating value would no longer increase significantly, but it would increase the corrosion to the equipment.

[0097] Based on the investigation of the above factors, several examples were made for the cases with more than two combinations, and their chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S tail gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) were tested.

[0098] Example 1

[0099] Sodium polyetheramine tetraacetate, tetrasodium N,N-diacetylethylenediamino-3-hydroxysuccinate (HAB), sodium polyacrylate, NaOH, Fe(NO3)3·9H2O and water are mixed, the weight percentage of iron ions is 4.5wt%, the molar ratio of the three chelating agents is 1:1:0.2, the molar ratio of chelating agent / Fe is 1:1, the pH value is adjusted to 8.0 with NaOH, and the mixture is mixed and reacted for 4 hours according to the preparation method to obtain the chelated iron desulfurizer 1.

[0100] Example 2

[0101] Tetrasodium N,N-diacetylethylenediamino-3-hydroxysuccinate (HAB), tetrasodium aspartic acid diacetate, fumaric acid-propylene sulfonic acid binary copolymer, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of the three chelating agents was 1:0.2, the molar ratio of chelating agent / Fe was 2:1, the pH value was adjusted to 11.0 with NaOH, and the mixture was mixed and reacted for 4 hours according to the preparation method to obtain the chelated iron desulfurizer 2.

[0102] Example 3

[0103] Sodium polyetheramine tetraacetate, tetrasodium aspartic acid diacetate, sodium polymethacrylate, NaOH, Fe(NO3)3·9H2O and water are mixed, the weight percentage of iron ions is 4.5wt%, the molar ratio of the three chelating agents is 1:1:0.2, the molar ratio of chelating agent / Fe is 3:1, the pH value is adjusted to 12 with NaOH, and the mixture is mixed and reacted for 4 hours according to the preparation method to obtain the chelated iron desulfurizer 3.

[0104] Example 4

[0105] HAB, tetrasodium 3-hydroxy-2,2′-iminodisuccinate (HIDS), water-soluble polymaleic anhydride, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of the three chelating agents was 1:1:4, the molar ratio of chelating agent / Fe was 5:1, the pH value was adjusted to 9.5 with NaOH, and the mixture was mixed and reacted for 4h according to the preparation method to obtain chelated iron desulfurizer 4.

[0106] Example 5

[0107] HAB, ethylenediamine disuccinic acid (EDDS), fumaric acid-propylene sulfonic acid binary copolymer, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of the three chelating agents was 1:3:1, the molar ratio of the chelating agent / Fe was 1:1, the pH value was adjusted to 10 with NaOH, and the mixture was mixed and reacted for 4h according to the preparation method to obtain the chelated iron desulfurizer 5.

[0108] Example 6

[0109] Sodium polyetheramine tetraacetate, iminodisuccinic acid (IDS), sodium polyacrylate, NaOH, Fe(NO3)3·9H2O and water are mixed, the weight percentage of iron ions is 4.5wt%, the molar ratio of the three chelating agents is 1:1:0.2, the molar ratio of chelating agent / Fe is 1.5, the pH value is adjusted to 9.5 with NaOH, and the mixture is mixed and reacted for 4 hours according to the preparation method to obtain the chelated iron desulfurizer 6.

[0110] Example 7

[0111] HAB, methylglycine diacetic acid (MGDA), sodium polyacrylate, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of the three chelating agents was 1:5:3, the molar ratio of chelating agent / Fe was 4:1, the pH value was adjusted to 9.5 with NaOH, and the mixture was mixed and reacted for 4h according to the preparation method to obtain the chelated iron desulfurizer 7.

[0112] Example 8

[0113] Sodium polyetheramine tetraacetate, glutamic acid oxalic acid (GLDA), sodium polyacrylate, NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of the three chelating agents was 1:2:6, the molar ratio of chelating agent / Fe was 1.5, the pH value was adjusted to 9.5 with NaOH, and the mixture was mixed and reacted for 4 hours according to the preparation method to obtain the chelated iron desulfurizer 8.

[0114] Comparison 1

[0115] Ethylenediaminetetraacetic acid (EDTA), NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 5.5wt%, the molar ratio of chelating agent / Fe was 3:1, the pH value was adjusted to 9.5 with NaOH, and the mixture was reacted for 4 hours according to the preparation method to obtain chelated iron desulfurizer a.

[0116] Comparison 2

[0117] Nitrilotriacetic acid (NTA), NaOH, Fe(NO3)3·9H2O and water were mixed, the weight percentage of iron ions was 4.5wt%, the molar ratio of chelating agent / Fe was 3:1, the pH value was adjusted to 9.5 with NaOH, and the mixture was reacted for 4h according to the preparation method to obtain chelated iron desulfurizer b.

[0118] Table 4 Comparison of the effects of the desulfurizer obtained in the examples of the present application with EDTA and NTA.

[0119] Desulfurization agent Chelating power in terms of Ca (mg / g) Chelating power in terms of Fe (mg / g) Desulfurization effect / % Total iron loss rate / % Chelating agent loss (g / L) <![CDATA[H2S tail gas greater than 250 ppm / min]]> ORP value / mV Regeneration time / min 1 160.8 168.9 100 1.7 0.31 31 -491.5 59 2 141.2 146.8 99.99 5.4 0.64 25 -445.1 72 3 156.8 160.8 99.99 2.5 0.42 30 -485.2 67 4 151.2 157.4 99.99 2.8 0.51 29 -478.4 60 5 150.8 154.8 99.99 3.1 0.53 27 -474.1 70 6 143.9 147.1 99.99 6.8 0.78 26 -446.8 75 7 149.6 152.3 99.99 3.6 0.55 27 -452.1 73 8 146.8 151.2 99.98 5.8 0.61 26 -450.2 70 a 52.6 64.5 99.25 20.3 1.78 11 -406.6 130 b 60.8 35.5 99.82 18.7 2.4 15 -416.5 120

[0120] The chelating force (calculated as Ca, mg / g), chelating force (calculated as Fe, mg / g), desulfurization effect (%), total iron loss rate (%), chelating agent loss (g / L), time when H2S tail gas is greater than 250ppm (min), ORP value (mV) and regeneration of iron ions (time / min) of desulfurizers 1-8 and desulfurizers a and b were tested, and the results are shown in Table 4. The results in Table 4 are analyzed, and combined with Test Examples 1-6, the present application chelated iron desulfurizer is composed of a high-price soluble iron salt, a chelating agent, a pH buffer and water; the chelating agent is a compound of polyetheramine tetraacetic acid sodium and N, N-diethylcarboxylic acid-based ethylenediamino-3-hydroxysuccinic acid, a polycarboxylic acid chelating agent or an amino acid derivative chelating agent; or the chelating agent is a compound of N, N-diethylcarboxylic acid-based ethylenediamino-3-hydroxysuccinic acid tetrasodium and polyetheramine tetraacetic acid sodium, a polycarboxylic acid chelating agent or an amino acid derivative chelating agent. Compared with the existing commonly used desulfurizers EDTA or NTA, the compounded chelated iron desulfurizer has significantly improved chelating ability, significantly enhanced iron ion regeneration ability, and a desulfurization effect comparable to EDTA or NTA.

[0121] The above is only an explanation of the invention process of the present application, and is not intended to limit the protection scope of the present invention. Therefore, all equivalent substitutions based on the inventive concept of the present application should be included in the protection scope of the present invention.

Claims

1. A chelated iron desulfurizer, consisting of a high-valent soluble iron salt, a chelating agent, a pH buffer and water, characterized in that: The chelating agent is a compound of sodium polyetheramine tetraacetate and at least one of N,N-diacetylethylenediamino-3-hydroxysuccinic acid, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent; or the chelating agent is a compound of tetrasodium N,N-diacetylethylenediamino-3-hydroxysuccinic acid and at least one of sodium polyetheramine tetraacetate, a polycarboxylic acid chelating agent or an amino acid-derived chelating agent; The polycarboxylic acid chelating agent is selected from water-soluble polymaleic anhydride or fumaric acid-propylene sulfonic acid binary copolymer, and the molecular weight of the water-soluble polymaleic anhydride is 400-800; The amino acid derived chelating agent is one or more of sodium epoxysuccinate-2-(hydroxyimino)malonate copolymer, tetrasodium iminodisuccinate, sodium aspartic acid diacetate, tetrasodium glutamate diacetate, trisodium methylglycine diacetate, dihydroxyethylglycine, and ethylenediamine disuccinic acid; The polyetheramine tetraacetic acid sodium and the N,N-diacetylethylenediamino-3-hydroxysuccinate tetrasodium are compounded in any ratio; When the polyetheramine tetraacetic acid sodium or N,N-diacetylethylenediamino-3-hydroxysuccinate tetrasodium is compounded only with the polycarboxylic acid chelating agent, the compounding ratio is 1:0.05-1:0.5; When polyetheramine tetraacetic acid sodium or N,N-diethylcarboxylic acid ethylenediamino-3-hydroxysuccinic acid tetrasodium is compounded only with an amino acid derivative chelating agent, the compounding ratio is (1-5): (1-3); The compounding ratio is a molar ratio.

2. The chelated iron desulfurizer according to claim 1, characterized in that: The average molecular weight of the sodium epoxysuccinate-2-(hydroxyimino)malonate copolymer is 180-400.

3. The chelated iron desulfurizer according to claim 1, characterized in that: The pH of the chelated iron desulfurizer is 8.0-13.

5.

4. The chelated iron desulfurizer according to claim 1, characterized in that: The molar ratio of the chelating agent to the soluble iron salt is 1:1-5:1, and the molar number of the soluble iron salt is calculated as high-valent iron ions.

Citation Information

Patent Citations

  • Composite chelated iron desulfurizing agent and preparation method thereof

    CN109758872A

  • Preparation method of novel environment-friendly chelating agent

    CN112430194A

  • Water-soluble polyether chelating agent as well as preparation method and application thereof

    CN113201130A

Cited By

  • Desulfurization of carbon dioxide-containing gases

    US12599868B2

  • Desulfurization of Carbon Dioxide-containing Gases

    US20240001288A1